THE MOST POPULAR DESTINATIONS FOR INTERNATION STUDENTS IN 2025 - Payziqulova Odina (Bright Mind Publishing, 2025)
This article explores the most popular study destinations and countries for international students in 2025. The article focuses on the unique education systems, student amenities, financial aid programs, and global opportunities of countries such as the United States, the United Kingdom, Canada, Australia, and Germany. The article also explores the reasons for the increase in the number of international students and their growing interest around the world. This will serve as a useful source of information for young people planning to study.
Keywords: International students, educational trends, global trends, popular countries, student visa, financial aid, 2025, education quality analysis.